Factors Related to Paracetamol Consumption among the Elderly in Saohai District, Saraburi Province - ปฏิญญา จักษุพันธ์; สุธีประเสริฐ, ธานินทร์; สุนทร, สุรศักดิ์; โกมลมาลัย, วัชรินทร์; ไล้สุวรรณชาติ, ปัญจรัตน์ (Journal of Health Science of Thailand, 2021)
Paracetamol is one of the most common drugs used as a pain reliever and a fever reducer. If it is used improperly, the drug can put health in jeopardy, especially among the elderly who are at greater risk. Such drug use requires intensive caution and appropriate dosage regimen. This descriptive research aimed to study paracetamol use behavior and factors relating to the usage behavior among the elderly in Sao Hai District, Saraburi Province. Data were collected from 363 subjects using a set of questionnaire with the reliability test of drug use knowledge at 0.69; with the enabling factors and the predisposing factors at 0.78 and 0.80, respectively. Data were analyzed and reported in frequency, percentage, arithmetic mean, standard deviation, maximum, minimum, Chi-square and Fisher’s Exact Test. Results showed that 62.3% of the subjects used paracetamol. Among them, 61.1% demonstrated correct utilization. For those with incorrect use, 81.8% used at incorrect timing, 28.4% used with wrong illness, and 3.4% with incorrect dosage. However, all subject reported correct route of administration. The factors sisnificantly associated with paracetamol use behavior included gender, age, marital status and enabling factors such as the influence from family members (p<0.05). Thus, there should be a campaign to reduce or discontinue the distribution of paracetamol in social events such as as a giveaway in the funeral ceremonies. Moreover, public health workers should be educate the elderly in the community on the rational drug use in order to prevent excessive or harmful use of paracetamol.